1988
DOI: 10.1111/j.1399-3054.1988.tb02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between water content and afterripening in red rice

Abstract: Reactions regulating seed dormancy can proceed at water contents which are probably too low to permit metabolic activity. The loss of dormancy via afterripening of red rice. (Oryza sativa L.) seeds was examined as a representative case. Equilibration of seeds to various moisture contents showed that afterripening was most rapid at 6–14% moisture content (dry weight basis). Afterripening did not occur at > 18% moisture content and was severely inhibited at < 5% moisture content. Seed viability was greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 13 publications
4
56
1
1
Order By: Relevance
“…Changes in AR50 in the autumn and spring occur when soil is moist (>20%) and seeds are therefore likely to be hydrated. This has significant ecological implications as it is widely considered that the release of dormancy via afterripening occurs in the dry state (14). Thus, in damp temperate soils, the rapid loss of dormancy occurring in hydrated seeds indicates that dry afterripening-traditionally considered to be the primary driving force for loss of dormancy (in both laboratory and field) (15-17)-may have a limited role during dormancy cycling in soil seed banks of temperate regions such as the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in AR50 in the autumn and spring occur when soil is moist (>20%) and seeds are therefore likely to be hydrated. This has significant ecological implications as it is widely considered that the release of dormancy via afterripening occurs in the dry state (14). Thus, in damp temperate soils, the rapid loss of dormancy occurring in hydrated seeds indicates that dry afterripening-traditionally considered to be the primary driving force for loss of dormancy (in both laboratory and field) (15-17)-may have a limited role during dormancy cycling in soil seed banks of temperate regions such as the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental conditions that facilitate afterripening vary by species. For example, rice normally requires afterripening under warm, dry conditions (Leopold et al, 1988) and Arabidopsis responds best to cool, moist conditions (Koornneef and Karssen, 1994). Rice species (Oryza ssp) differ in patterns of afterripening under warm, dry conditions (Veasey et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Leopold, Glenister and Cohn (1988) found that in red rice the best response to after ripening was obtained when seeds are treated between 6 and 14% at 22°C which belongs to water binding region of 1 and 2. That region of water isotherms is involved non-enzymatic oxidative reactions in seed (Priestley 1986).…”
Section: Discussionmentioning
confidence: 98%
“…Vertucci and Leopold (1984) found that there are three regions of water-binding the seed components and these help for interpretation of various biochemical processes which can occur in seeds as a function of water content. Region 1 and 2 involves nonenzymatic oxidation, while region 3 is identified as the uptake of oxygen with production of CO2 (Vertucci and Leopold 1986) Leopold, Glenister and Cohn (1988) showed that afterripening red rice occurred between 6 and 14% moisture content which includes parts of water -binding region 1 and 2. In okra, hardseededness as well as afterripening treatment efficiency is related to seed moisture.…”
Section: Introductionmentioning
confidence: 99%